A STUDY ON IMPACT OF WORKING LIFE BANANCE ON EMPLOYEE RETENTION: A STUDY EDUCATION SECTOR IN LUCKNOW - Singh, Srishti; Srivastava, Asha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study is an attempt to investigate the factors of employees’ retention in the Education sector of Lucknow and find out its impact on the performance of Education sector. Employee’s retention is major and vital issue facing by the Education industry in Lucknow because of the shortage of skilled employment, economic growth as whole and employee turnover. Lucknow is a economic hub and highly depends upon Education activities but Education sector are facing difficulties to manage their policies regarding motivation, training and development. Therefore it requires long term planning to cover the future related problem in this field which should be realized today. With the increasing attrition in organizations especially in Indian Public Sector Organization, it has become a question of study. Employee retention is beneficial for the organization as well as to the employee. This paper deals with factors that are affecting the retention of employees in Indian Public/Private Sector Organization and its impact on the Organization. This study focuses on the primary data, which has been collected through closed ended questions with a five point Likert Scale. The study uses purposive sampling technique to capture the response of bankers. The collected data has been examined and evaluated through Statistical Package for Social Sciences (SPSS). The results of data have been critically examined through each and every angle and hence, we reached on the finding of the research. This study concluded that there is a strong relationship between Employees’ motivation and employees’ retention among employees of Education whereas employees’ training and development has no relationship with employees’ retention. It is suggested that Education sector should mold their policies regarding employees’ training and development, which will help Education sector to retain employees for longer time.